Opportunities and challenges of targeting c-Met in the treatment of digestive tumors - Zhang, Zhengchao; Li, Dong; Yun, Heng; Tong, Jie; Liu, Wei; Chai, Keqiang; Zeng, Tongwei; Gao, Zhenghua; Xie, Yongqiang (Frontiers in Oncology, 2022)
At present, a large number of studies have demonstrated that c-Met generally exerts a crucial function of promoting tumor cells proliferation and differentiation in digestive system tumors. c-Met also mediates tumor progression and drug resistance by signaling interactions with other oncogenic molecules and then activating downstream pathways. Therefore, c-Met is a promising target for the treatment of digestive system tumors. Many anti-tumor therapies targeting c-Met (tyrosine kinase inhibitors, monoclonal antibodies, and adoptive immunotherapy) have been developed in treating digestive system tumors. Some drugs have been successfully applied to clinic, but most of them are defective due to their efficacy and complications. In order to promote the clinical application of targeting c-Met drugs in digestive system tumors, it is necessary to further explore the mechanism of c-Met action in digestive system tumors and optimize the anti-tumor treatment of targeting c-Met drugs. Through reading a large number of literatures, the author systematically reviewed the biological functions and molecular mechanisms of c-Met associated with tumor and summarized the current status of targeting c-Met in the treatment of digestive system tumors so as to provide new ideas for the treatment of digestive system tumors.